PERSEPSI RUMAHTANGGA TANI TERHADAP USAHATANI TERNAK SAPI POTONG (Studi di Desa Kanigoro Kecamatan Pagelaran-Malang) - Eko Nugroho; Priyo Sugeng Winarto (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
The research was conducted at Kanigoro Village in Pagelaran Sub-District, District of Malang from May to July 2003. The Objectives of the research are (1) describing the perception of farm household about small scale cattle farm, (2) studying about the factors which influence farm household’s access to cattle in Kanigoro Village. Forty five farmers were selected using purposive random sampling method. Descriptive and economic farming system analysis were applied to the data available. The research found that farm households who kept cattle have perception that rearing cattle could be used for saving, used for land cultivation (i.e brujul) and covered leisure as well. Farm households who did not keep cattle have perception that they had lack of family labour, preferring to rear other ruminants (i.e goats, buffaloes and milking cows) and did not have enough cash to buy cattle. The factors which influence farm household’s access to cattle were difficulties in accessing feed resources (i.e grass), fluctuated cattle price and difficulties in finding the share holders (penggaduh). Based on these, it is suggested that preliminary research concerning the perception of the local farm households to cattle farming, feed resources and labour availability should be conducted prior to establish an area as the centre of cattle farming development.